Blood Ties (Spirit Animals Book 3). - Nix, Garth; Williams, Sean. (New York Scholastic, 2014)
The adventure continues in this third book in the New York Times bestselling series.Erdas is a land of balance. A rare link, the spirit animal bond, bridges the human and animal worlds. Conor, Abeke, Meilin, and Rollan each have this gift-and the grave responsibility that comes with it. But the Conquerors are trying to destroy this balance. They're swallowing whole cities in their rush for power-including Meilin's home. Fed up with waiting and ready to fight, Meilin has set off into enemy territory
M
b
M